A geomorphological and hydrological underpinning for archaeological research in northern Qatar - Macumber, Phillip G. (Proceedings of the Seminar for Arabian Studies, 2011)
This paper examines occupation and settlement in northern Qatar in terms of a physical (geomorphological and hydrogeological) and temporal (climatic and eustatic) framework. Under the present arid/hyper-arid climate and low relief there is no perennial surface water. Potable water was obtained from groundwater, which occurs as a fresh-water lens overlying saline water; it was accessed by hand-dug wells which were concentrated closer to the coast where the freshwater table is shallowest. There is a close relationship between water table level depth under the Qatar peninsula and sea level, which was mostly lower than at present in Late Quaternary times, being at minus 120-130 m about 18,000 years ago and minus 40 m 10,000 years ago. During the Epipaleolithic, Upper Palaeolithic, and much of the Middle Palaeolithic periods back to the end of the last wet interglacial (Eemian) from 117,000-130,000 years ago, sea levels were low and groundwater was deep and unattainable, making permanent occupation unlikely. The onset of the Indian Ocean Monsoon in the Early Holocene overlapped with high interglacial sea levels in the mid-Holocene, providing a Hydrological Optimum from c.7000 to c.6000 years BP, when sea level reached c.3 m above that at present. Water was readily available with the likelihood of significant coastal spring outflow, at a time before the development of the saline coastal sabkha, where outflowing groundwater is now lost. It corresponds to the period of some of the most important pre-Islamic archaeological sites in Qatar, situated on the high-level shoreline at al-Shaqrā՚ D , al-Khawr, and across the Aburuk (al-Burūq) peninsula/Dasah (Daՙsah)/Dukkan (Dukhān) area. The high retreat of the monsoon at c. 6000 years BP ushered in a period of shallow hand-dug wells with settlements concentrated nearer the coast, especially in the north where the freshest groundwater occurs. This phase lasted until c. 1960 when the introduction of large wells and bores with modern pumps greatly reduced the size of the freshwater lens causing up-coning of salt water into the wells and salinization of the coastal aquifers by seawater intrusion.